การสังเคราะห์งานวิจัยของสาขาวิชาการบริหารการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยเชียงใหม่ ระหว่างปีการศึกษา 2555 – 2556 - สมชาย พันธุ์สันติกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aims to synthesize the 86 subjects of education administration researches of faculty of Education in Chiang Mai University during the academic year 2555 – 2556. The tools used in this study were the synthesis researches form and analysis notes document. Synthesis-oriented features data was analyzed by frequency, percentage and content analysis in each category. The study result found that all synthesized researches were an independent study and were approved in the year 2555, the most synthesized researches were studied by teachers, and aim to develop education domain. The synthesized researches used both population and sample. The most used tool was a questionnaire which was manually created by researcher, and the efficiency of the questionnaire was analyzed by checking the validity. Then the researcher collected the data by himself. The result was divided into the five following categories: Category 1 finding on executive education, the good features of executive education were leadership, human relationship, ability to work, self-development, and practice skill. The executive education played a role in promoting learning management which includes 5 fields: Curriculum development, measurement and evaluation, classroom management research, learning resource management and the educational supervision. Category 2 finding on the education administration procedure, the study showed that the education administration consisted business management. The steps of education administration procedure were to study current issues, demand planning, implementation and evaluation of plans. Moreover the school administrators have to perform at a high level. However, there are the main problems significant in personnel management, administration budget and the process. Category 3 finding on responsibilities of executive administration, the study found that the responsibilities executive administration was divided into four fields: Academic administration, administration, budget and finance administration, the general management. The overall operations of the schools in the four departments were at high levels. Category 4 finding were on the administration information. The commission found that the role of the Basic Education Commission and the community was supporting education in every aspect except academic planning, finance and budget and personnel management which are less involved. Category 5 finding were on other context. The study found that Thailand was trying to create a unified administration, but there are so many factors making that cause separate the primary and secondary education office service Area. In addition, the operations assessment of the institutions in another context showed the most operating was at a high level. The concordance between researches and education development plan of the Ministry of Education No. 11 showed the most researches consistent with the education of the Ministry of Education No. 11. They should publish and promote more about researches and enhance the students to work on practical research. For further study the students/researchers should design researches quality and diversity tools for the researches. In addition they should also study about government plan of study in the future, the study direction of other organization which relates to each field of study. .